logo for solving-math-problems.com
leftimage for solving-math-problems.com

6th Grade Math - Parentheses - PEMDAS











































PEMDAS: Where do the parenthesis go?

2.8+5-3=2

9x0+5-3=4

Comments for 6th Grade Math - Parentheses - PEMDAS

Click here to add your own comments

Sep 08, 2011
Parentheses – PEMDAS - Puzzle
by: Staff



The question:


PEMDAS: Where do the parenthesis go?

2.8+5-3=2

9x0+5-3=4


The answer:

Problem 1:

2.8 + 5 - 3 = 2



To make this expression = 2, you must insert more than one set of parentheses:

= 2((.8(+5) - 3))


You can now use PEMDAS to check the result, step by step:

PEMDAS order tells you what to do first, second, . . . etc.

PEMDAS order stands for: parentheses, exponents, multiplication, division, addition, subtraction

You should begin by evaluating the expression inside each set of PARENTHESES

There are THREE NESTED sets of PARETHESES. Begin by evaluating the INNERMOST PARENTHESES:

(+5)

= 5

The expression now looks like this:

= 2((.8*5 - 3))


The original innermost parentheses has been replaced with *5.

There are now only TWO NESTED sets of PARENTHESES. You should first evaluate the expression inside the INNERMOST PARENTHESES:

= (.8*5 - 3)

= (4 - 3)

= (1)

= 1

The expression now looks like this:

= 2*1

The innermost parentheses has been replaced with *1.


= 2*1

= 2


Summary:

2((.8(+5) - 3)) = 2



------------------------------------------------------


Problem 2: 9x0 + 5 – 3 = 4

I couldn’t find any placement of parentheses which would equal 4.

Is it possible that the = 4 should be = 42 ?

If the = 4 is changed to = 42, the solution is as follows:

9*(0 + 5) - 3 = 42

As before, you can now use PEMDAS to check the result, step by step:

You should begin by evaluating the expression inside each set of PARENTHESES

There is only ONE set of PARENTHESES.

= (0 + 5)

= (+ 5)

= (5)

= 5

The expression now looks like this:

= 9*5 - 3 = 4


When you apply PEMDAS to this expression, the multiplication must be completed before the subtraction:

= 45 - 3

= 42



Summary:

9*(0 + 5) - 3 = 42




Thanks for writing.

Staff
www.solving-math-problems.com




Click here to add your own comments

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.



Copyright © 2008-2015. All rights reserved. Solving-Math-Problems.com